PHYSICAL ACTIVITY, DIETARY HABITS AND FAMILY HISTORY AS RISK FACTORS FOR ACUTE APPENDICITIS IN ADOLESCENTS. A CASE-CONTROL STUDY (The Research of Medical Science Review, 2025)
Background: Acute appendicitis is the most common surgical emergency worldwide. Its incidence is higher in the second and third decades of life. The exact cause of acute appendicitis is unknown, although luminal obstruction, genetic factors, infections, and environmental factors may contribute to its development.Objectives: To investigate the physical activity, dietary habits and family history as risk factors for acute appendicitis in adolescents.Methods and materials: This case-control study was conducted from March 2024 to March 2025 in three tertiary care hospitals in Peshawar (Khyber Teaching Hospital, Lady Reading Hospital, and Hayatabad Medical Complex). The cases and controls were selected based on predefined inclusion and exclusion criteria. The data collection tool was a structured questionnaire. After obtaining consent and briefly explaining the questionnaire, it was distributed among the participants. Any missing responses were addressed on the spot. The data was analysed by using SPSS version 20. The chi-square and independent t tests were applied, and a p-value <0.05 was considered statistically significant.Results: 120 participants were taken, including 60 cases and 60 controls. In both the appendicitis and control groups, males and females were 41 (68.3%) and 19 (31.7%), respectively. The mean age of the appendicitis group was 15.0±3.14 years, compared to the control group (15.5±3.49). The study revealed a significant association between family history and the development of acute appendicitis (p=0.001, OR=3.35, 95% CI:1.12- 10.0), with a higher proportion of the appendicitis group reporting positive family history 14 (23.33%) as compared to a control group 5 (8.33%). Low fibre intake was more prevalent in the appendicitis group, 38 (63%), than in the control group, 27 (45%), showing a significant link with acute appendicitis risk (p= 0.044, OR=2.11, CI 95%: 1.06-4.21). This study showed that those with acute appendicitis were considerably less physically active than the controls (p <0.001).Conclusion: Family history and a low-fibre diet may contribute to the development of acute appendicitis, while engaging in physical activity may reduce the risk. Further studies are needed to strengthen these findings.